(untitled) (Research, Society and Development, 2020)
The aim of this study was to analyze the determinants of healthy aging in a group of elderly people assisted by the Family Health Strategy in Belém/Pará. Cross-sectional study carried out with 279 elderly people registered in a Family Health Strategy in the city of Belém-PA, from January to March 2014. Data were collected according to the determinants of healthy aging (cross-sectional and economic, social, environmental and Cheers). For the analysis of the data, the Statistical Package for Social Science Program version 20.0 was used. Among the results obtained, among the elderly, 65.2% were female and 34.8%, male. The largest proportion of them were in the 60 to 69 age group; 53.0% had low income and 59.5% had low education. As risk factors for aging, falls were identified in 52.0%, more than 75% had some health problem; 70.3% of women were sedentary and about 63.7% of them were hospitalized. It was evidenced in this study that the majority of the elderly presented damage to healthy aging, such as risk of falls, physical inactivity and low income, especially among women. In this sense, the manuscript’s contribution to collective health consists of presenting the scenario that outlines healthy aging within an FHS, allowing the planning of specific interventions.